STRATEGI PEMASARAN KRIPIK NANGKA PADA CV. KAJEYEFOOD (Study kasus: CV. KajeyeFood Kecamatan Blimbing, Kota Malang) - Astrid Sukma Asri (Program Studi Agribisnis, 2020)
This research aims to that is: to calculate the level of business efficiency of chips nangka, to know the strengths, weaknesses, opportunities, and the threat of business chips nangka, to know the strategy that can be applied in the marketing of chips products Jackfruit in the village of Polosesame District Blimbing Malang. The determination of the research site is purposive (intentionally) in the village of Polosesame District Blimbing Malang. With the data analysis methods used are: calculating the business efficiency level, the IFE matrix and EFE for the company, the IE matrix to know the position of the company, the SWOT matrix to formulate the alternative marketing strategy, and QSPM to decided the priority of the marketing strategy of jackfruit.